Experimental study on operation limit of ground heat exchanger based on ground source heat pump unit - Rui Zhang (PLoS ONE, 2025)
The heat transfer performance of a ground heat exchanger (GHE) directly influences the operational performance of a ground source heat pump (GSHP) system. The fluid temperature within the GHE is constrained by the protective temperature limits of the GSHP unit. Specifically, the inlet water temperature has an upper limit in summer and a lower limit in winter. These temperature limits further affect the heat exchange efficiency between the GHE and the surrounding soil. In this study, an experimental station featuring a single U-shaped GSHP system was constructed, and a three-dimensional model of the system was developed. Experiments were conducted by operating one or two GHEs to investigate the heat transfer per unit well depth and the matching relationship between cooling capacity and indoor load when the inlet water temperature of the heat pump unit approaches its summer and winter limits. In summer, when operating a single GHE, the heat transfer per unit well depth reached 134.4 W/m at an inlet temperature of 45 °C. When the cooling supply just matched the cooling load demand, the heat transfer per unit well depth was 131.5 W/m. However, prolonged operation led to a scenario where the cooling supply could no longer meet the load demand. In winter, operating a single GHE resulted in a heat transfer per unit well depth of 43.95 W/m at an inlet temperature of 5 °C. These results indicate that when the number of heat exchangers is insufficient, the inlet water temperature of the heat pump unit may reach or exceed the limit value, leading to decreased unit efficiency. Additionally, inadequate heat exchange between the GHE and the soil results in insufficient cooling or heating capacity, failing to meet the indoor load requirements.